(untitled) (Global Journal of Management and Business Research, 2019)
Demonetization is a concept which came into existence to make green banking more successful. This action lead to a powerful reaction on the online banking which gives more preference to green banking. So demonetization is a strategy to create awareness among the rural and urban citizens with regard to the usage of green banking services. Green banking is ethical bank which encourages the online transactions by reducing the carbon footprint from the regular banking activities. Demonetization has spread the wider message to all the people of the country about to increase the cashless transaction, where as green banking is totally about to give more preference to cashless transaction. So there is a great impact of demonetization on green banking services.